CESifo World Economic Survey February 2009 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2009)
World Economic Climate: World Economic Climate deteriorates further - Economic Expectations: Assessments of the current economic situation and economic expectations downgraded - Inflation: Higher inflation expected in 2008 - Interest Rates: Decline of interest rates expected - Currencies: US dollar remains undervalued - Special Topic: Doha Round of trade negotiations
Keywords: 330